ANALISIS PENDAPATAN USAHA DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PERUSAHAAN KONSTRUKSI DI BURSA EFEK INDONESIA - Lesly, Novalia; Yuliadi, Yuliadi (SCIENTIA JOURNAL, 2020)
This study aims to analyze the effect of operating income and operating costs on net income of construction companies in the Indonesia Stock Exchange for the period 2015-2019. It is known that the dependent variable is business income and operational costs, while the independent variable is net income. The population in this study were 16 companies selected using the purposive sampling method. The type of data used is secondary data so that data in the form of annual financial reports are obtained from the Indonesia Stock Exchange. This research method uses quantitative methods because it is in the form of financial statement data. This study uses multiple linear regression analysis and a sample of 8 (eight) construction companies on the Indonesia Stock Exchange (IDX) in the form of financial statements from the period 2015-2019. Financial statement data obtained from the Indonesia Stock Exchange website (www.idx.co.id). The analytical tool used in this research is the SPSS (Statistical Product and Service Solutions) version 25. Based on the t test results, that partially operating income has a significant effect on net income with tcount of 6.088> ttable 2.026 and operational costs do not significantly influence profit net with tcount 0.915 <ttable 2.026. Then where the results of the F test simultaneously, that operating income and operating costs affect net income, by producing a value of Fcount 103.991> Ftable 3.252. The value of R square (R2) in this study explains that variations in changes in operating income and operating costs affect net income of 84.1%. While the remaining 15.9% can be said in other respects or said outside the variables of this study.